2016
DOI: 10.1002/eat.22592
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling body image: The relative associations of overvaluation, dissatisfaction, and preoccupation with psychological distress and eating disorder behaviors in male and female adolescents

Abstract: Objective: The distinctiveness and relative clinical significance of overvaluation, dissatisfaction, and preoccupation with body weight/shape remains inconclusive. This study sought to add to the evidence by testing associations between these three body image constructs and indicators of clinical significance.Method: Male and female secondary students (N 5 1,666) aged 12-18 years completed a survey that included measures of dissatisfaction with, overvaluation of, and preoccupation with weight/ shape, psycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
91
2
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 117 publications
(105 citation statements)
references
References 36 publications
10
91
2
2
Order By: Relevance
“…The pattern of findings are also in support of the focus of the gender additive model of depression on body dissatisfaction (Bearman & Stice, 2008), as the current study shows that body dissatisfaction is the aspect of body image disturbance that is most consistently associated with depressive symptoms. However, these findings do stand in contrast to those of Mitchison, Hay, et al (2017), who found that dissatisfaction was not associated with psychological distress once the role of other aspects of body image (preoccupation, overvaluation) had been taken into account. One potential explanation is that while in the current study we measured general body dissatisfaction with a range of body parts (including height, face, shoulders, etc.…”
Section: Discussioncontrasting
confidence: 98%
See 4 more Smart Citations
“…The pattern of findings are also in support of the focus of the gender additive model of depression on body dissatisfaction (Bearman & Stice, 2008), as the current study shows that body dissatisfaction is the aspect of body image disturbance that is most consistently associated with depressive symptoms. However, these findings do stand in contrast to those of Mitchison, Hay, et al (2017), who found that dissatisfaction was not associated with psychological distress once the role of other aspects of body image (preoccupation, overvaluation) had been taken into account. One potential explanation is that while in the current study we measured general body dissatisfaction with a range of body parts (including height, face, shoulders, etc.…”
Section: Discussioncontrasting
confidence: 98%
“…To some extent the specificity of the associations with preoccupation found in the current study mirrors the results of Mitchison, Hay, et al (2017). Although Mitchison, Hay, et al (2017) did not find an exclusivity of preoccupation’s association with disordered eating outcomes, they did find that preoccupation was the strongest independent predictor of dietary restraint and binge eating, particularly in girls.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations